Precision spectroscopy and comprehensive analysis of perturbations in the A1∏(v = 0) state of 13C18O. (2nd January 2019) - Hakalla, R.; Trivikram, T. M.; Heays, A. N.; Salumbides, E. J.; de Oliveira, N.; Field, R. W.; Ubachs, W.
ABSTRACT: We have reinvestigated the A level of 13 C 18 O using new high-resolution spectra obtained via multi-photon laser excitation as well as with synchrotron-based Fourier-transform absorption spectroscopy of the A, e, d, a, and a bands. In addition, Fourier-transform emission spectroscopy in the visible range is performed on the band. Spectra of the B band are measured in order to tie information from the latter emission data to the level structure of A . The high pressures in the absorption cell at the synchrotron and the high temperatures in the emission discharge permitted monitoring of high rotational quantum levels in A up to J =43. All information, in total over 900 spectral lines, was included in an effective Hamiltonian analysis of the A levels that are directly perturbed by the e, d, a, D, I close-lying levels and the e, d, a remote levels, as well being indirectly influenced by the a state. The influence of 9 further perturber levels and their interactions was investigated and are not significant for reproducing the present experimental data. This analysis leads to a much improved description in terms of molecular constants and interaction parameters, compared to previous studies of the same energy region for other CO isotopologues. GRAPHICAL ABSTRACT: